Multilevel current source inverter to improve power quality in a distribution network - Aguirre, Miguel Pablo (2010)
This paper deals with the problem of reactive power and harmonics in a standard medium voltage (MV) distribution network. It presents the design of a shunt active filter implemented with a multilevel current source inverter (MCSI) connected to the medium voltage level of a power distribution system. The proposed MCSI is made by identical modules where all inductors carry the same amount of current. The current balance is achieved by a Phase-Shifted Carrier SPWM proper implementation. The performance of proposed active filter is thoroughly simulated with Matlab Simulink. It shows very good behavior in steady state and transient conditions.